2005
DOI: 10.1097/01.brs.0000148047.31164.f1
|View full text |Cite
|
Sign up to set email alerts
|

Course of Spinal Solitary Osteochondromas

Abstract: Study Design. Six spinal solitary osteochondromas.Objectives. To evaluate the course of spinal cord compression after surgery, and the risk of local recurrence and malignant transformation, based on the present series and cases reported in the literature.Summary of Background Data. Spinal cord compression by a solitary osteochondroma is rare. Little is known concerning neurologic improvement after decompression of the spinal cord or the risk of recurrence or malignant transformation of spinal solitary osteocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 34 publications
1
69
0
1
Order By: Relevance
“…In most series, patients present with pain, weakness, or other significant neurologic findings [4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Roach et al found that 12 out of 44 patients screened had lesions encroaching into the spinal canal and, thus, recommended routine magnetic resonance imaging (MRI) or computed tomography (CT) screening of the neuroaxis in patients with MHE to detect compressive lesions prior to the onset of neurologic deficits [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…In most series, patients present with pain, weakness, or other significant neurologic findings [4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Roach et al found that 12 out of 44 patients screened had lesions encroaching into the spinal canal and, thus, recommended routine magnetic resonance imaging (MRI) or computed tomography (CT) screening of the neuroaxis in patients with MHE to detect compressive lesions prior to the onset of neurologic deficits [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…In our case, the patient's father and grandmother had HME, so we could easily make the diagnosis of HME preoperatively. Malignant transformation may occur in up to 20% of patients with HME 4,10) . These exostosis, also called osteochondromas, involve the vertebral column in approximately 7-9% of cases, and 50% of these cases arise from the cervical spine 5) .…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the surgical outcome is good and laminectomy is the most common treatment method 4) . However, to prevent postlaminectomy kyphosis, laminectomy should be minimized, especially, in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, surgical treatment was reported to improve the neurological deficit in nearly %90 of cases of spinal cord compromise caused by solitary osteochondromas. No adjuvant therapy is necessary after the surgery (1,2,4,6,7,8,10,13).…”
Section: Case Reportmentioning
confidence: 99%
“…Only 1.3 to 4.1% of solitary osteochondromas involve the spine and are usually asymptomatic (1). A few cases suffering from leg pain or sciatica by solitary lumbar osteochondroma have been reported in the English medical literature (1)(2)(3)(4)6,7,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%